An Estimate of the Importance of Electron-stimulated Desorption of Sodium at Mercury - Rosemary M. Killen; Jason L. McLain; Matthew H. Burger; Orenthal J. Tucker; Liam S. Morrissey; Ronald J. Vervack Jr. (The Planetary Science Journal)
We revisit the importance of electron-stimulated Desorption (ESD) as a source of neutral sodium (Na) atoms and Na ^+ ions in Mercury’s exosphere and ionosphere. For the first time we have calibrated the ESD yield per electron as a function of electron energy in the energy range 100–950 eV. This calibrated yield per electron was convolved with the electron flux as a function of energy onto Mercury’s cusps to determine the average release rate of Na ^+ to the exosphere, using electron flux and cusp area estimates from a recent hybrid magnetosphere model. Given that previous work showed the ESD yields per electron of Na ^+ ions and neutral Na atoms are approximately equal, we compared the energy-weighted ESD release of Na ^+ to that deriving from micrometeoroid impact vaporization, photon-stimulated desorption, and ion sputtering. We conclude that ESD is not a significant source of neutral Na atoms or Na ^+ ions to Mercury’s exosphere.